Development Of Props Media “Smiling Clock” For Teaching Speaking Skill - Khamidah, Niswatul; Rofi’ah, Siti; Widiarini, Widiarini (Jurnal Ilmiah Mandala Education (JIME), 2023)
In the seventh grade of MTs Ma'arif Kawedusan, it was found that the understanding of English material was relatively low, because there weren't enough learning tools available to spark kids' interest in studying English.The purpose of the research is to develop props media Smiling Clock for teaching the speaking of telling time material.. In this learning media development research used the ADDIE method, where in this method researchers carried out as many as five stages. Analysis, design, development, implementation, and evaluation. After going through several processes until the product was finished, the researcher validated it. The first validation, the instrument validation, was based on instrument experts' evaluations, it received a score of 93% with the category "Very Valid". The second validation the media validation, was based on media experts evaluations, it received a score of 81% with the category "Valid". The last validation, the material validation was based on  material experts’ evaluation, it received a score of 90% with the criteria "Very Valid". Furthermore, revise the product according to the advice of media experts, products that are ready to be tested on students. Trials on students obtained data from student responses to learning, the percentage of answers from student responses that met the standard of "Very Good" was 91%. By considering the result of the research, it can therefore say that the props media Smiling Clock can be used for effective and efficient learning.